Rice price inflation dynamics in the Philippines - Antonio, Ronald Jeremy; Valera, Harold Glenn; Mishra, Ashok K.; Pede, Valerien O.; Yamano, Takashi; Vieira, Bernardo Oliva (Wiley, 2025)
This study examines the monthly regional dynamic relationship between rice price inflation and its key drivers in the Philippines using a panel vector auto‐regression model over the period January 1994–March 2023. We find evidence that the effect of a world rice price shock is generally larger and more persistent than the effects of other factors. We also find that movements in rice price inflation are explained by domestic fuel price shocks and, to a lesser extent, by world urea price shocks. The impulse response functions driven by those three shocks vary over the sample, especially before a change in food policy such as the imposition of the rice tariffication in 2019. Further analysis suggests that El Niño Southern Oscillation shocks tend to induce an inflationary effect on rice prices in high‐poverty and rice‐sufficient regions. Our results have important food policy implications for rice markets and offer timely insights into the desirability of current proposals to help lower and stabilise rice prices for consumers and improve existing support for farmers to boost rice production.